IMPEDIMENTS OF COACHING PRACTICES IN THE PUBLIC UNIVERSITY - Tabao, Mark John (International Journal of Arts, Sciences and Education, 2022)
Abstract It’s possible that an athlete’s level of motivation is one of the most important factors in determining whether or not they will be successful. Athletes are subjected to a wide range of external pressures throughout the entirety of their time spent competing in a sport, and each of these influences has the potential to have an effect on the athletes’ level of motivation as well as their overall performance. The methodology that was used in the formulation of this study was one that focused on description and correlation. The descriptive design is used with the intention of characterizing the coaches’ profiles, as well as their coaching styles and behaviors, in order to better understand the relationship between the two. The research approach was utilized in order to successfully complete this task. On the other hand, the primary focus of the correlational design was on the gathering of data or information to establish the link between two or more variables that were the subject of the inquiry. This relationship was the subject of the inquiry. Using the design itself to carry out research allowed us to achieve this goal. The study provided evidence to support the hypothesis that coaches’ pedagogical approaches differ according to their age and the level of competition they have attained. It also suggests that the profiles of the coaches are not essential to an understanding of the differences in the approaches that coaches take to teaching, which is also true with regard to coaching styles. According to what has been observed, coaches face scheduling conflicts in two different ways. One concern is how effectively they divide their time between coaching and carrying out their responsibilities as a teacher in the classroom. The author came to the conclusion that a lack of equipment and facilities is one of the difficulties that are experienced by both coaches and players. It cannot be denied that proper coaching and training need facilities and equipment that are both practical and suitable for the purpose. This will, as a direct consequence, lead to improved athletic performance.